F01. Paroxysmal fast activity and genetic generalized epilepsies. (May 2018) - Suresh, Niraja; Cruz, Angelica; Jayakody, Himali; Benbadis, Selim R.
Abstract : Introduction: Paroxysmal fast activity is the hallmark of "symptomatic generalized" epilepsy of the Lennox Gastaut type, often occurring with slow spike-wave complexes. Generalized, synchronous epileptiform discharges are considered the typical abnormality on EEG in genetic generalized epilepsy (GGE). Recent literature suggests that generalized paroxysmal fast activity (GPFA) may occur in the context of GGE, and may contribute to clinical heterogeneity. Here, we present three patients with generalized fast spike-wave discharges and polyspikes with concurrent GPFA. Methods: Institutional databases of EEG tracings and the electronic medical records were reviewed for cases of GPFA with an electro-clinical diagnosis of GGE. Results: All three patients had onset of their seizures in childhood from age 8–13. Two of the three had mild cognitive impairment. MRI of all three patients were unremarkable. Their seizures were all medically intractable, requiring at least 3–5 broad spectrum antiepileptic drugs, and all 3 were recommended to pursue or chose to have a vagal nerve stimulator implanted. Seizure subtypes included generalized tonic clonic (most frequent) followed by automotor, myoclonic, and astatic seizures. All three EEGs showed brief generalized spike-wave complexes at 3–6 Hz lasting 1–4 s, and generalized paroxysmal fast activity (12–20 Hz) lasting 5–20 s. One tracing showed evolution of GPFA to polyspikes that correlated to a clinical myoclonic seizure. Conclusion: GPFA is classically associated with symptomatic generalized epilepsies of the Lennox-Gastaut type, but these three cases demonstrate GPFA can be seen in GGE. Such patients may be more refractory than the usual GGE, and may belong on a continuum between GGE and LGS.